2013
DOI: 10.1002/jgrd.50313
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface roughness and soil texture on mineral dust emission fluxes modeling

Abstract: [1] Dust production models (DPM) used to estimate vertical fluxes of mineral dust aerosols over arid regions need accurate data on soil and surface properties. The Laboratoire Inter-Universitaire des Systemes Atmospheriques (LISA) data set was developed for Northern Africa, the Middle East, and East Asia. This regional data set was built through dedicated field campaigns and include, among others, the aerodynamic roughness length, the smooth roughness length of the erodible fraction of the surface, and the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 73 publications
1
106
1
Order By: Relevance
“…A future development would be to include a roughness length map instead of a using fixed roughness length for land use categories (e.g. Menut et al, 2013b), which is particularly relevant for areas which are classified as desert but in which the nature of this desert varies strongly per region. This could be achieved relatively easily.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…A future development would be to include a roughness length map instead of a using fixed roughness length for land use categories (e.g. Menut et al, 2013b), which is particularly relevant for areas which are classified as desert but in which the nature of this desert varies strongly per region. This could be achieved relatively easily.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Good modelling of mineral dust emissions is a challenge and results from different models are easily a factor of 10 apart. This is because generation of windblown dust is very sensitive to local wind speed and to regional and local roughness length (Menut et al, 2013b) and soil char- acteristics (Mokhtari et al, 2012). Therefore all models use tuning factors to come to optimal settings for the region of interest.…”
Section: Aerosol Modelling Improvementmentioning
confidence: 99%
“…In addition to this version, several processes were improved and added in the framework of this study. First, the mineral dust emissions are now calculated using new soil and surface databases, (Menut et al, 2013b) and with a spatial extension of potentially emitting areas in Europe as described in Briant et al (2014).…”
Section: Chimere Chemistry-transport Modelmentioning
confidence: 99%
“…The meteorological modeling was already done and evaluate with the WRF model, for the same kind of domain and resolution as in and Menut et al (2013b, c) for example. It was shown that the model is able to accurately reproduce the main meteorological variables over the Euro- Mediterranean area: the day-to-day and hourly variabilities are well reproduced for all variables, the biases are known and the model representativity is adapted to the main variations of gaseous and aerosol formation and transport.…”
Section: Modeled Meteorology Evaluationmentioning
confidence: 99%
See 1 more Smart Citation